Is enrichment culture necessary for the isolation of Campylobacter jejuni from faeces? - Hutchinson, D N (1983)
The role of enrichment culture for the isolation of Campylobacter jejuni from faeces is discussed. It is concluded that enrichment culture is only necessary for those specimens where it is anticipated that the number of organisms is likely to be low. In a trial of a blood free enrichment broth (CCD broth) and the modified Preston enrichment broth the latter gave significantly superior results.